2009
DOI: 10.1097/hjh.0b013e32831967ca
|View full text |Cite
|
Sign up to set email alerts
|

Stroke risk and antihypertensive drug treatment in the general population: the Japan arteriosclerosis longitudinal study

Abstract: Treated individuals with optimal BP had a higher stroke risk than untreated ones with optimal BP. Healthcare providers need to be vigilant for residual cardiovascular risks in treated hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 37 publications
2
40
2
Order By: Relevance
“…Furthermore, we estimated the absolute disease risks for incident CVD associated with different levels of BP in the community and demonstrated that treated hypertensives had a greater risk of incident CVD compared with untreated participants with similar BP. These observations are in line with the results from population‐based analyses from Japan and Sweden reporting greater risks of cardiovascular mortality and stroke in treated versus untreated persons 9, 10, 11. Finally, we report that the increased hazard for CVD is attenuated by ≈3% to 20% on adjustment for the greater subclinical disease burden in treated hypertensives, consistent with the concept that part of the increased CVD risk is related to the greater subclinical disease burden.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we estimated the absolute disease risks for incident CVD associated with different levels of BP in the community and demonstrated that treated hypertensives had a greater risk of incident CVD compared with untreated participants with similar BP. These observations are in line with the results from population‐based analyses from Japan and Sweden reporting greater risks of cardiovascular mortality and stroke in treated versus untreated persons 9, 10, 11. Finally, we report that the increased hazard for CVD is attenuated by ≈3% to 20% on adjustment for the greater subclinical disease burden in treated hypertensives, consistent with the concept that part of the increased CVD risk is related to the greater subclinical disease burden.…”
Section: Discussionsupporting
confidence: 90%
“…Previous observational studies, unlike clinical trials, have also found residual cardiovascular risk in treated hypertensive subjects. [32][33][34] Antihypertensive medication use in observational studies probably indicates more severe hypertension, not just the effect of treatment. In addition, the period during which antihypertensive medication has been used as well as the age at which the treatment was initiated could also contribute to the apparent risk.…”
Section: Discussionmentioning
confidence: 99%
“…13,[27][28][29][30][31][32][33] Likewise, a number of large-scale cohort studies have reported significant effects of prehypertension separately on the risks of stroke 13,29,30,32 and coronary heart disease. 13,29 The present analysis from the APCSC confirmed the results from the previous observational studies and provided more detailed information about the separately significant associations of prehypertension with all of the major types of CVD, including ischemic and hemorrhagic stroke in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%